2020
DOI: 10.14814/phy2.14630
|View full text |Cite
|
Sign up to set email alerts
|

The effect of succinic acid on the metabolic profile in high‐fat diet‐induced obesity and insulin resistance

Abstract: Obesity, insulin resistance, and poor metabolic profile are hallmarks of a high‐fat diet (HFD), highlighting the need to understand underlying mechanisms. Therefore, we sought to determine the effect of succinic acid (SA) on metabolism in high‐fat diet (HFD)‐induced obesity. Animals were randomly assigned to either low‐fat diet (LFD) or a high‐fat diet (HFD). Mice consumed their respective diets for 4.5 months and then assigned to the following groups: (LFD)+vehicle, LFD + SA (0.75 mg/ml), HFD + vehicle, or HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Both 30 mW/cm 2 and 80 mW/cm 2 LIPUS significantly increased the serum L-alanine level of hind limb unloading rats. In this study, we found that succinic acid as a key metabolite affects the metabolic balance, which is similar to the results of skeletal muscle metabolic abnormality model, in which succinic acid was found to induced the biosynthesis of mitochondria, promote the increase of the number of mitochondria, and enhance the respiratory capacity of oxidative skeletal muscle, and proposed that the significant decrease of succinic acid content in hind limb unloading may be related to the biosynthesis [69].Aspartic acid plays a variety of functions in physiological and biological processes and is a non-essential amino acid in mammals [70].Aspartic acid is used for the biosynthesis of nucleotides and proteins, and also plays an important role in skeletal muscle metabolism [71]. For example, aspartic acid supplementation can regulate muscle glucose uptake and improve muscle utilization of excess fatty acids and glycogen in rats [72,73].…”
Section: Discussionsupporting
confidence: 84%
“…Both 30 mW/cm 2 and 80 mW/cm 2 LIPUS significantly increased the serum L-alanine level of hind limb unloading rats. In this study, we found that succinic acid as a key metabolite affects the metabolic balance, which is similar to the results of skeletal muscle metabolic abnormality model, in which succinic acid was found to induced the biosynthesis of mitochondria, promote the increase of the number of mitochondria, and enhance the respiratory capacity of oxidative skeletal muscle, and proposed that the significant decrease of succinic acid content in hind limb unloading may be related to the biosynthesis [69].Aspartic acid plays a variety of functions in physiological and biological processes and is a non-essential amino acid in mammals [70].Aspartic acid is used for the biosynthesis of nucleotides and proteins, and also plays an important role in skeletal muscle metabolism [71]. For example, aspartic acid supplementation can regulate muscle glucose uptake and improve muscle utilization of excess fatty acids and glycogen in rats [72,73].…”
Section: Discussionsupporting
confidence: 84%
“…It is necessary to investigate the active components in amber extract, and our previous studies have attempted to identify the components using HPLC. Succinic acid, a major component of amber, has been reported to increase the production of heat by brown adipose tissue [ 21 ] and suppress lipid accumulation [ 22 ]. Recently, it has been reported that succinate accumulation in hypoxic adipose tissue contributes to lipolysis and insulin resistance [ 23 ], suggesting that exogenous succinic acid could promote lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, epididymal adipose tissue (EAT) mass was assessed in YG mice (n = 8) and a subset of AG (n = 6) and PAR2KO-AG (n = 8) mice. Though we have previously documented that EAT and NMR are highly related [ 15 ]. The remaining AG and PAR2KO-AG mice were not euthanized and used for a separate study.…”
Section: Methodsmentioning
confidence: 99%